Prevalensi Ektoparasit pada Kambing Kacang di Kecamatan Prambon Kabupaten Nganjuk - Nining Sari Virgandina Vinola; Agus Sunarso; Nenny Harijani; Endang Suprihati; Poedji Hastutiek; Mufasirin Mufasirin (Journal of Parasite Science (JoPS), 2020)
The purpose of this research are to identify and prevalence of ectoparasite infestation in bean goats on the sub-district of Prambon, district of Nganjuk. The research was conducted from September until December 2019 with 115 samples of bean goats. The samples were identified in the Entomology and Protozoology Laboratory of Parasitology Department of the Veterinary Faculty of Airlangga University. This research use non-experimental method with survey study. This research found several kind of extoparasites that infestation bean goats, as follows: Bovicola caprae 24.3% the most infestation in dorsal region, Linognatus africanus 31.2% the most infestation in head-neck and dorsal region, Ctenocepallides felis 4.3%. Mix infestation found B. Caprae and L. Africanus 20.8%, B. Caprae and C. Felis 1%, B. Caprae, L. Africanus and C. Felis 1%. This ectoparasite usually found infestatio in head-neck, ventral, dorsal, inguinal, and ectremites. The prevalence of ectoparasites is 82.6% area at sub-district of Prambon, district of Nganjuk. The data analyzed using Chi-square test and Correspondence test. Statistically is no significant association (p>0.05) between the prevalence of ectoparasites that infested bean goats with types of stage and non-stage eclosure. This caused due to environmental conditions are dirty and many other livestock around the cage.